A MFI type flake molecular sieve and preparation method thereof

By using alcohol solvents to regulate crystal growth in molecular sieve synthesis, the MFI-type sheet molecular sieve with thinner b-axis direction is directly synthesized, which solves the problem of carbon accumulation in traditional microporous molecular sieve, simplifies the preparation process, reduces costs, and improves catalysis Reaction performance, suitable for industrial applications.

CN115321556BActive Publication Date: 2024-12-17THE NORTHWEST RES INST OF CHEM IND +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211023999.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2024-12-17
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

Traditional microporous molecular sieves have problems with carbon deposits in diffusion mass transfer and catalytic reactions, resulting in a decrease in reaction activity. Existing methods such as the introduction of second pores or nano-sized molecular sieves have problems such as the problem of complex preparation, high cost or difficulty in scale.

Method used

By adding alcohols as crystal growth regulators to the synthesis of molecular sieve, the MFI-type sheet molecular sieve with thinner b-axis direction is directly synthesized by one-step method to regulate the thickness and proportion of molecular sieve in different axial directions, shorten the diffusion path, and use the The hydrogen bonding of alcohol solvents inhibits crystal surface growth.

Benefits of technology

It has achieved simplification of the preparation process, shortening the crystallization time, reducing synthesis costs, improving catalytic reaction performance, and enhancing the resistance of the carbon deposits of molecular sieves, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115321556B_ABST
    Figure CN115321556B_ABST
Patent Text Reader

Abstract

The present invention discloses an MFI type sheet-like molecular sieve, wherein the length of the molecular sieve in the b-axis direction is 70-100 nm, and the length ratio L between the b-axis and the a-axis direction is b / L a Less than 0.40. The molecular sieve is a ZSM-5 molecular sieve or an S-1 molecular sieve. At the same time, a preparation method of the MFI type flaky molecular sieve is also disclosed, by adding an alcohol substance as a crystal growth regulator for molecular sieve synthesis, no secondary aging is required, and a one-step method can be used to directly synthesize the flaky molecular sieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieves, and in particular relates to an MFI type sheet molecular sieve and a preparation method thereof. Background Art

[0002] MFI type molecular sieves are molecular sieves with double ten-membered ring cross channels, and typical representatives are ZSM-5 molecular sieves and pure silicon S-1 molecular sieves.

[0003] As an important microporous material, ZSM-5 molecular sieve has broad application prospects in industrial catalysis, industrial waste gas treatment and other fields due to its unique ten-membered ring cross-pores, adjustable acid sites and good hydrothermal stability. However, since traditional microporous molecular sieves only have microporous channels, when macromolecular reactants or products pass through the microporous channels, diffusion and mass transfer are easily restricted, resulting in the formation of a large amount of carbon deposits and blocking of the channels, resulting in reduced molecular sieve reaction activity.

[0004] The mass transfer limitation problem of traditional microporous molecular sieves can be effectively solved by shortening the diffusion path inside the zeolite (Journal of the American Chemical Society, 2021, 143(4):1993-2004.). At present, the main methods to shorten the diffusion path include: 1) introducing a second pore (mesopore or macropore) into the microporous structure of zeolite; 2) reducing the size of the molecular sieve crystal to the nanoscale to synthesize nanomolecular sieves; 3) regulating the proportion of each crystal face of the molecular sieve, especially synthesizing a sheet molecular sieve with a thickness of nanometers in the b-axis direction (Journal of the American Chemical Society, 2019, 141:3772-3776.). Generally, the introduction of mesopores or macropores into the molecular sieve crystal by post-treatment or template method (hard template method and soft template method) can increase the diffusion rate, increase the specific surface area, and enhance the molecular sieve's ability to resist carbon deposition. However, the former has problems such as complicated preparation steps and the generation of waste alkali liquid to pollute the environment, and the latter has problems such as the expensive template agent required and the high synthesis cost. In addition, by nano-sizing the zeolite particles, that is, reducing the size of the molecular sieve to below 100 nm, the mass transfer distance of the reactant molecules in the pores can be shortened and the diffusion performance of the molecular sieve can be improved. However, this method has problems such as the molecular sieve particles being too small and difficult to separate, which limits its large-scale application in actual production processes.

[0005] By adjusting the axial length of the crystal along the straight channel / sinusoidal channel of the molecular sieve (the straight channel is along the b axis, the sinusoidal channel is along the a axis and c axis) and the ratio of each axis, in particular, the synthesis of thin sheet molecular sieves in the b axis direction can shorten the diffusion path, which to a certain extent solves the problems of diffusion mass transfer and catalytic deactivation caused by the single microporous channel of the molecular sieve. Katz et al. (Journal of the American Chemical Society, 2014, 136(4): 1449-61.) prepared borosilicate nanosheet molecular sieves by layering layered borosilicate zeolite precursors with Al(NO3)3 aqueous solution. Roth et al. (Journal of the American Chemical Society, 2021, 143(29): 11052-11062.) used tetrabutylammonium hydroxide for the first time to directly exfoliate layered MCM-56 and ZSM-55 zeolite precursors into monolayer nanosheets. However, the above-mentioned synthesis method of the exfoliated precursor requires two-step post-treatment, and the preparation steps are cumbersome. At the same time, the organic surfactants or organic amines used in the process will cause environmental pollution and other problems, limiting the application of this method in industry. Ryoo et al. (Nature, 2009, 461(7261): 246-249.) used a self-designed and synthesized template containing organic bifunctional groups - diquaternary ammonium salt to prepare an MFI type molecular sieve with a b-axis thickness of about 4nm (~2 unit cells), and showed relatively excellent catalytic performance in macromolecular catalytic reactions, but the expensive price of the organic template limits the application prospects of this method in industry. In recent years, Xiao Fengshou's research group (2010, 47(3):1048-1050.) reported the addition of urea to the synthesis of gel mother liquor to synthesize TS-1 nanosheet molecular sieves with a thickness of about 80nm, and successfully extended the preparation strategy of urea-assisted synthesis of TS-1 nanosheets to the preparation of ZSM-5 nanosheets. Li Landong's research group (Journal of the American Chemical Society, 2021, 143 (4): 1993-2004.) reported a method for synthesizing nanosheet molecular sieves by ammonium fluoride-assisted low-temperature crystallization, in which the b-axis thickness of the synthesized molecular sieve is only tens of nanometers, and the size range of the a and c axes is micrometer level. The above-mentioned method of directly adding a crystal growth regulator to the gel mother liquor to synthesize nanosheet molecular sieves is simple and efficient, and the synthesis cost is low, which is conducive to potential industrial applications, but the current problem is that the synthesis process of this method requires two-step aging, and the crystallization time is long. Therefore, it is necessary to explore a method for synthesizing a faster crystallization synthesis of a flaky molecular sieve with adjustable crystal face ratio. Summary of the invention

[0006] In view of the defects of the prior art, the present invention provides an MFI type flaky molecular sieve and a preparation method thereof. By adding alcohol substances as crystal growth regulators for molecular sieve synthesis, no secondary aging is required, and the flaky molecular sieve can be directly synthesized in one step.

[0007] An MFI type sheet-like molecular sieve, wherein the length of the molecular sieve in the b-axis direction is 70-100 nm, and the length ratio L of the b-axis to the a-axis direction is b / L a Less than 0.40.

[0008] Preferably, the molecular sieve is ZSM-5 molecular sieve or S-1 molecular sieve.

[0009] A method for preparing an MFI type flaky molecular sieve comprises the following steps:

[0010] (1) Dissolve the alkali source in deionized water, stir until it is clear, add the template agent, stir until it is clear, then drop the silicon source, stir for 2-4 hours, and finally add ethanol, continue stirring for 1-2 hours to obtain a molecular sieve precursor;

[0011] (2) placing the molecular sieve precursor obtained in step (1) into a hydrothermal synthesis reactor, sealing it, and crystallizing it at 80-210° C. for 2-48 hours;

[0012] (3) After the crystallization is completed, solid-liquid separation is performed, and the separated solid is washed with deionized water until it is neutral, and then dried and calcined to prepare a pure silicon S-1 flaky molecular sieve.

[0013] Preferably, in step (1), when the alkali source is dissolved in deionized water, an aluminum source is also added to the deionized water to prepare a ZSM-5 flaky molecular sieve.

[0014] Preferably, the alcohol solvent is one of methanol, ethanol, isopropanol and n-butanol.

[0015] Preferably, the amount of silicon source is calculated as SiO2, the amount of alkali source is calculated as NaOH, and the molar ratio of silicon source, template, alcohol solvent, alkali source and deionized water in step (1) is 30: (5-30): (300-2000): (0.5-3): (300-4000).

[0016] Preferably, the amount of silicon source is calculated as SiO2, the amount of aluminum source is calculated as Al2O3, and the amount of alkali source is calculated as NaOH. The molar ratio of silicon source, aluminum source, template, alcohol solvent, alkali source and deionized water in step (1) is 30: (0.3-1.0): (5-30): (300-2000): (0.5-3): (300-4000).

[0017] Preferably, the silicon source is at least one of tetraethyl orthosilicate, silica sol and white carbon black.

[0018] Preferably, the alkali source is selected from at least one of alkali metal hydroxides.

[0019] Preferably, the template is tetrapropylammonium hydroxide.

[0020] Preferably, the aluminum source is at least one of aluminum isopropoxide, aluminum hydroxide, aluminum sulfate, aluminum nitrate, and sodium aluminate.

[0021] Preferably, in step (2), crystallization is performed at 120-180° C. for 4-24 h.

[0022] More preferably, in step (2), crystallization is performed at 150-170° C. for 8-12 h.

[0023] Preferably, the drying in step (3) is carried out at 80-100°C for 8-10 hours; and the calcination in step (3) is carried out at 400-600°C for 5-8 hours.

[0024] In the present invention, the added alcohol solvent, on the one hand, acts as a template for the synthesis of the molecular sieve, has a regulating effect on the nucleation and crystallization process of the molecular sieve, and can change the size of the molecular sieve; at the same time, on the other hand, acts as a crystal inhibitor. The hydroxyl group (-OH) of the alcohol with a higher dielectric constant is more likely to react with the silanol group (Si-OH) of the

[010] crystal plane of the molecular sieve to form a hydrogen bond, and the hydrophobic alkane group of the alcohol inhibits the growth of the zeolite crystal on the

[010] crystal plane, so that the growth of the molecular sieve in the b-axis direction is inhibited, which is conducive to the formation of a sheet-like molecular sieve with a thin b-axis thickness.

[0025] In the present invention, the higher the ethanol concentration, the longer the molecular sieve is in the c-axis direction and the shorter in the b-axis direction. Meanwhile, the crystallization temperature and the crystallization time also affect the morphology of the molecular sieve. As the crystallization temperature increases, the particle size of the flaky molecular sieve gradually increases. In the crystallization process, nanocrystalline particles in a metastable state are first formed, and then the ethanol dispersed in the gel system forms "Si-OC" by dehydrating the "Si-OH" of the

[010] crystal face of the crystal grain, thereby inhibiting the growth of the

[010] crystal face of the crystal grain, and finally forming a molecular sieve with a flaky morphology.

[0026] Advantages of the present invention:

[0027] (1) In the present invention, cheap alcohol solvents are selected as crystal growth regulators for molecular sieve synthesis. By appropriately adding alcohol solvents to the molecular sieve gel mother liquor, as well as ethanol produced by self-hydrolysis when the silicon source is tetraethyl orthosilicate, the morphology of the molecular sieve can be changed, and the thickness and axial ratio of the molecular sieve in different axes can be regulated to generate a sheet-like molecular sieve.

[0028] (2) By adding alcohol solvents to the gel mother liquor of molecular sieve synthesis, no secondary aging is required, the crystallization time is short, and the MFI type flaky molecular sieve can be directly synthesized in a simple step. This preparation method is simple, has high synthesis efficiency, and relatively cheap raw materials, and is worth promoting on a large scale.

[0029] (3) The sheet-like molecular sieve prepared by the present invention can shorten the diffusion path of reactant and product molecules in the pores, reduce the carbon deposition rate of the molecular sieve, thereby improving the catalytic reaction performance and increasing the reaction life.

[0030] (4) The present invention selects a renewable alcohol solvent, which is cheap and renewable, and conforms to the strategic concept of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 SEM image of the ZSM-5 molecular sieve prepared in Example 1;

[0032] Figure 2 SEM image of the ZSM-5 molecular sieve prepared in Example 2;

[0033] Figure 3 SEM image of the ZSM-5 molecular sieve prepared in Example 3;

[0034] Figure 4 SEM image of the ZSM-5 molecular sieve prepared in Example 5;

[0035] Figure 5 SEM image of the ZSM-5 molecular sieve prepared in Example 6;

[0036] Figure 6 SEM image of the S-1 molecular sieve prepared in Example 8;

[0037] Figure 7 XRD pattern of the ZSM-5 molecular sieve prepared in Example 1;

[0038] Figure 8 XRD pattern of the S-1 molecular sieve prepared in Example 8. DETAILED DESCRIPTION

[0039] Example 1

[0040] 1. A method for preparing an MFI type flake molecular sieve, specifically a ZSM-5 flake molecular sieve, comprising the following steps:

[0041] (1) Sodium aluminate is used as an aluminum source, sodium hydroxide is used as an alkali source, tetraethyl orthosilicate is used as a silicon source, tetrapropylammonium hydroxide is used as a template, and ethanol is selected as an alcohol solvent; sodium aluminate and sodium hydroxide are dissolved in deionized water, and after being fully stirred until clarified, tetrapropylammonium hydroxide solution is added thereto, and fully stirred until clarified to form a mixed alkali solution, and finally tetraethyl orthosilicate is slowly added thereto, and after vigorous stirring for 3 hours, ethanol is added thereto, and stirring is continued for 1 hour to obtain a molecular sieve precursor; wherein the amount of the silicon source is calculated as SiO2, the amount of the aluminum source is calculated as Al2O3, and the amount of the alkali source is calculated as NaOH, and the molar ratio of the silicon source, the aluminum source, the template, the alcohol solvent, the alkali source and the deionized water is 30: 1: 5: 300: 1.5: 4000;

[0042] (2) placing the molecular sieve precursor obtained in step (1) into a hydrothermal synthesis reactor, sealing it, and crystallizing it at 170° C. for 12 h;

[0043] (3) After the crystallization is completed, solid-liquid separation is performed, and the separated solid is washed with deionized water until it is neutral, and then dried at 80°C for 10 hours and calcined at 400°C for 8 hours;

[0044] The ZSM-5 molecular sieve obtained in this example was analyzed by SEM. Figure 1 .Depend on Figure 1 It can be seen that its morphology is nanosheet-like and uniform in size. By counting its lengths in the a-axis, b-axis, and c-axis directions and taking the average value as the length of each axis, it can be concluded that its lengths in the a-axis, b-axis, and c-axis directions are 90 nm and 1440 nm, respectively, and the length ratio of the b-axis to the a-axis direction is L b / L a is 0.27;

[0045] At the same time, XRD analysis of the ZSM-5 molecular sieve obtained in this example showed Figure 7 ,Depend on Figure 7 It can be seen that it is a typical MFI-type characteristic peak, with no other impurity peaks and good crystallinity.

[0046] Example 2

[0047] The amount of ethanol is increased, wherein the molar ratio of silicon source, aluminum source, template, alcohol solvent, alkali source and deionized water is 30: 1: 5: 2000: 1.5: 4000, and the other conditions are the same as those in Example 1, and the prepared MFI type flaky molecular sieve is ZSM-5 molecular sieve;

[0048] The obtained ZSM-5 molecular sieve was subjected to SEM analysis. Figure 2 .Depend on Figure 2It can be seen that its morphology is chopstick-shaped nanosheets with uniform size. The lengths of the a-axis, b-axis, and c-axis are counted and the average value is taken as the length of each axis. It can be concluded that the lengths of the a-axis, b-axis, and c-axis are 644 nm, 72 nm, and 4100 nm, respectively. The length ratio of the b-axis to the a-axis is L b / L a is 0.11.

[0049] Example 3

[0050] The amount of deionized water used is reduced, the molar ratio of silicon source, aluminum source, template, alcohol solvent, alkali source and deionized water is 30: 1: 5: 2000: 1.5: 300, and the other conditions are the same as those in Example 1. The prepared MFI type flaky molecular sieve is ZSM-5 molecular sieve;

[0051] The obtained ZSM-5 molecular sieve was subjected to SEM analysis. Figure 3 The morphology is observed to be nanosheet-like and uniform in size. The lengths of the a-axis, b-axis, and c-axis directions are counted and the average value is taken as the length of each axis. The lengths of the a-axis, b-axis, and c-axis directions are 336 nm, 97 nm, and 720 nm, respectively. The length ratio of the b-axis to the a-axis direction is L b / L a It is 0.29.

[0052] Example 4

[0053] The silicon-aluminum ratio is different, the amount of aluminum source is reduced, the molar ratio of silicon source, aluminum source, template, alcohol solvent, alkali source and deionized water is 30: 0.375: 5: 2000: 1.5: 4000, and the other conditions are the same as those in Example 1. The prepared MFI type flaky molecular sieve is ZSM-5 molecular sieve;

[0054] The obtained ZSM-5 molecular sieve was subjected to SEM analysis, and its morphology was observed to be nanosheet-like and uniform in size. Its lengths in the a-axis, b-axis, and c-axis directions were counted, and the average value was taken as the length of each axis. It was found that its lengths in the a-axis, b-axis, and c-axis directions were basically close to those in Example 1.

[0055] Example 5

[0056] The amount of template added is increased, the molar ratio of silicon source, aluminum source, template, alcohol solvent, alkali source and deionized water is 30: 1: 30: 2000: 1.5: 4000, and the other conditions are the same as those in Example 1. The prepared MFI type flaky molecular sieve is ZSM-5 molecular sieve;

[0057] The obtained ZSM-5 molecular sieve was subjected to SEM analysis. Figure 4The morphology is observed to be nanosheet-like and uniform in size. The lengths of the a-axis, b-axis, and c-axis directions are counted and the average value is taken as the length of each axis. The lengths of the a-axis, b-axis, and c-axis directions are 308 nm, 82 nm, and 970 nm, respectively. The length ratio of the b-axis to the a-axis direction is L b / L a is 0.27.

[0058] Example 6

[0059] The crystallization temperature is 150°C, and the other conditions are the same as those in Example 1. The prepared MFI-type flaky molecular sieve is a ZSM-5 molecular sieve;

[0060] The obtained ZSM-5 molecular sieve was subjected to SEM analysis. Figure 5 The morphology is observed to be nanosheet-like and uniform in size. The lengths of the a-axis, b-axis, and c-axis directions are counted and the average value is taken as the length of each axis. The lengths of the a-axis, b-axis, and c-axis directions are 271 nm, 89 nm, and 503 nm, respectively. The length ratio of the b-axis to the a-axis direction is L b / L a It is 0.33.

[0061] Example 7

[0062] The crystallization time is 8 hours, and the other conditions are the same as those in Example 1. The prepared MFI-type flaky molecular sieve is a ZSM-5 molecular sieve;

[0063] The obtained ZSM-5 molecular sieve was subjected to SEM analysis, and its morphology was observed to be nanosheet-like and uniform in size. Its lengths in the a-axis, b-axis, and c-axis directions were counted, and the average value was taken as the length of each axis. It was found that its lengths in the a-axis, b-axis, and c-axis directions were basically close to those in Example 1.

[0064] Example 8

[0065] No aluminum source was added, and the other conditions were the same as in Example 1. The prepared MFI type flaky molecular sieve was pure silicon S-1 molecular sieve;

[0066] The S-1 molecular sieve was subjected to SEM analysis, and its morphology was observed to be nano-sheet-like with uniform size. Its lengths in the a-axis, b-axis, and c-axis directions were counted, and the average value was taken as the length of each axis. The lengths in the a-axis, b-axis, and c-axis directions were 300 nm, 98 nm, and 1600 nm, respectively. The length ratio of the b-axis to the a-axis direction was L b / La is 0.33;

[0067] At the same time, XRD analysis of the S-1 molecular sieve obtained in this example showed Figure 8 ,Depend on Figure 8 It can be seen that it is a typical MFI-type characteristic peak, with no other impurity peaks and good crystallinity.

Claims

1. An MFI type sheet molecular sieve, characterized in that: The length of the molecular sieve in the b-axis direction is 70-100 nm, and the length ratio L between the b-axis and the a-axis direction is b / L a Less than 0.40; The MFI type flaky molecular sieve is prepared by the following method: (1) dissolving an alkali source in deionized water, stirring until clarified, adding a template thereto, stirring until clarified, then dropping a silicon source thereto, stirring for 2-4 hours, and finally adding an alcohol solvent thereto, continuing to stir for 1-2 hours, to obtain a molecular sieve precursor; the alcohol solvent is ethanol; (2) placing the molecular sieve precursor obtained in step (1) into a hydrothermal synthesis reactor, sealing it, and crystallizing it at 80-210 °C for 2-48 h; (3) After the crystallization is completed, solid-liquid separation is performed, and the separated solid is washed with deionized water until it is neutral, and then dried and calcined; The amount of silicon source is calculated as SiO2, the amount of alkali source is calculated as NaOH, and the molar ratio of silicon source, template, alcohol solvent, alkali source and deionized water in step (1) is 30: (5-30): (300-2000): (0.5-3): (300-4000).

2. The MFI type sheet molecular sieve according to claim 1, characterized in that: The molecular sieve is S-1 molecular sieve.

3. The MFI type sheet molecular sieve according to claim 1, characterized in that: In step (1), when the alkali source is dissolved in deionized water, an aluminum source is also added to the deionized water at the same time, and the obtained MFI type flaky molecular sieve is a ZSM-5 molecular sieve.

4. The MFI type sheet molecular sieve according to claim 3, characterized in that: The amount of silicon source is calculated as SiO2, the amount of aluminum source is calculated as Al2O3, and the amount of alkali source is calculated as NaOH. The molar ratio of silicon source, aluminum source, template, alcohol solvent, alkali source and deionized water in step (1) is 30: (0.3-1.0): (5-30): (300-2000): (0.5-3): (300-4000).

5. The MFI type sheet-like molecular sieve according to claim 1 or 4, characterized in that: The silicon source is at least one of ethyl orthosilicate, silica sol, and white carbon black; The alkaline source is selected from at least one of alkali metal hydroxides; The template agent is tetrapropylammonium hydroxide.

6. The MFI type sheet-like molecular sieve according to claim 3 or 4, characterized in that: The aluminum source is at least one of aluminum isopropoxide, aluminum hydroxide, aluminum sulfate, aluminum nitrate, and sodium aluminate.

7. The MFI type sheet-like molecular sieve according to claim 1, characterized in that: In step (2), crystallization is performed at 120-180°C for 4-24 hours; in step (3), drying is performed at 80-100°C for 8-10 hours; and in step (3), calcination is performed at 400-600°C for 5-8 hours.

Citation Information

Patent Citations

  • Intergrowth molecular sieve and method for synthesizing same

    CN101279743A

  • Preparation method of hierarchical pore TS-1 nano zeolite aggregation molecular sieve

    CN107915234A

  • Synthesis method of flaky MFI topological structure molecular sieve

    CN112850740A

  • Method for producing zeolite membrane composite body and zeolite membrane composite body

    JP2021045711A